Psychometric Analysis of an Instrument Evaluating Students’ Acceptance of Online Platform to Support Online English Learning - Sulthonah, Fathia Amalia; Mulyono, Herri; Wan Ahmad, Wan Fatimah (Jurnal Pendidikan Indonesia, 2022)
Acceptance of technology takes as a crucial role in context of the technology adoption. Before encouraging the maximal use of technology, it is important that users have to first acknowledge its use and that they have to also accept it. The current study was proposed in aims to examine the validity and the reliability of the Indonesian version of instrument investigating TAM constructs such as perceived usefulness, perceived ease of use, and behavioural intention. The questionnaire was adopted to elaborate the undergraduate students’ technology acceptance of WhatsApp, Google Classroom, and Microsoft Teams as online platform to support online English learning based on the Technology Acceptance Model (TAM). Data were collected from 370 undergraduate students from different universities in Indonesia and the study applied Rasch analysis technique to address the Rasch assumptions such as items dimensionality, person and item reliability, person and item mapping, rating scale, and differential items functioning measure. The findings of the study suggested that the adopted and translated to Indonesian questionnaire was found to be sufficient in context of psychometric characteristics and was considered eligible to measure the technology acceptance of online platforms used for English online learning.